2010
DOI: 10.1111/j.1469-8137.2010.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuber melanosporum: mating type distribution in a natural plantation and dynamics of strains of different mating types on the roots of nursery‐inoculated host plants

Abstract: Summary• In light of the recent finding that Tuber melanosporum, the ectomycorrhizal ascomycete that produces the most highly prized black truffles, is a heterothallic species, we monitored the spatial distribution of strains with opposite mating types (MAT) in a natural truffle ground and followed strain dynamics in artificially inoculated host plants grown under controlled conditions.• In a natural truffle ground, ectomycorrhizas (ECMs), soil samples and fruit bodies were sampled and genotyped to determine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
142
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 46 publications
(104 reference statements)
7
142
2
1
Order By: Relevance
“…The first analyses confirmed that the genetic individuals forming the gleba were also present on surrounding mycorrhizae [6,7], establishing evidence for the trophic link between fruitbodies and tree roots by way of the maternal parent. Moreover, labelling of tree photosynthates by 13 [ 6 1 _ T D $ D I F F ] CO 2 successfully demonstrated the transfer of carbon from leaves to fruitbodies [8], supporting the nutritional role of maternal individuals.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The first analyses confirmed that the genetic individuals forming the gleba were also present on surrounding mycorrhizae [6,7], establishing evidence for the trophic link between fruitbodies and tree roots by way of the maternal parent. Moreover, labelling of tree photosynthates by 13 [ 6 1 _ T D $ D I F F ] CO 2 successfully demonstrated the transfer of carbon from leaves to fruitbodies [8], supporting the nutritional role of maternal individuals.…”
mentioning
confidence: 99%
“…The monitoring of trees in a nursery after inoculation by black truffle spores [6] suggested that although individuals with both mating types coexisted on young seedlings, one of the mating types was progressively excluded over time (Figure 2). The underlying mechanism is not yet fully understood, but a role for vegetative incompatibility has been suggested [6,10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In some populations, only one mating type can be found under a single host tree (Murat et al 2013) (Table 1). In other populations, Rubini et al (2011a), Zampieri et al (2012), and Linde and Selmes (2012) found biased distributions of two mating types of Tuber truffles under a single tree. Because sexual reproduction in Tuber species requires the mating between strains of two different mating types, the mycetophagous mammals play an important role for this to occur by bringing sexual partners into the proximity of root resident strains (Kataržytė and Kutorga 2011).…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 95%